ANALISIS PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT MAHASISWA UNTUK BERWIRAUSAHA: IAIN Langsa Nangroe Aceh Darussalam - Zainal Abidin dkk; ZAINAL ABIDIN, AGUSTINAR, NUR AZIZAH DAN MAULINA ULFANUR (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2020)
Abstract This study aims to determine the magnitude of the direct and indirect influence of education variables, family environment on student interest in entrepreneurship. The type of research to be carried out in this study uses a survey method, while the approach to be used is a quantitative approach. The research population is all students of Islamic Economic Law (HES) IAIN Langsa who have taken entrepreneurship courses. This research was conducted at the Faculty of Sharia, Sharia Economic Law Study Program (HES) in the IAIN Langsa campus area. And when the research will be conducted in December 2017. The results of this study are the results of the first test show that education affects the family environment by 96% with t count 39.05> 1.67. The second test of the family environment affects interest 40.65> 1.67. Future research requires the application of entrepreneurship or direct practice to the field for students at the Faculty so that they better understand and export themselves in the world of entrepreneurship.